From Parent-Child Mutuality to Security to Socialization Outcomes: Developmental Cascade toward Positive Adaptation in Preadolescence - Kim, Sanghag (Attach Hum Dev, 2015)
A developmental cascade from positive early parent-child relationship to child security with the parent to adaptive socialization outcomes, proposed in attachment theory and often implicitly accepted but rarely formally tested, was examined in 100 mothers, fathers, and children followed from toddler age to preadolescence. Parent-child Mutually Responsive Orientation (MRO) was observed in lengthy interactions at 38, 52, 67, and 80 months; children reported their security with parents at age 8. Socialization outcomes (parent- and child-reported cooperation with parental monitoring and teacher-reported school competence) were assessed at age 10. Mediation was tested with PROCESS (Hayes, 2013). The parent-child history of MRO significantly predicted both mother-child and father-child security. For mother-child dyads, security mediated links between history of MRO and cooperation with maternal monitoring and school competence, controlling for developmental continuity of the studied constructs. For father-child dyads, the mediation effect was not evident.